Liderazgo directivo y clima organizacional en una institución educativa Iquitos 2025 - Tuesta Rucoba, Sofia Carolina (2025)
The purpose of this research was to determine how managerial leadership and organisational climate are related in an educational institution, Iquitos 2025. The study was a basic, non-experimental, cross-sectional design. The sample was taken from the total population of 60 teachers. In the results, 13.3% responded that the management leadership variable was bad and 60.0% said it was good. On the organisational climate variable, 10.0% responded that it was bad and 53.3% that it was good. Likewise, the chi-square test yielded a significance value of 0.0000<0.05, indicating that there is a direct relationship between managerial leadership and organisational climate in an educational institution, Iquitos 2025.